EVALUATION OF EDUCATIONAL ACHIEVEMENTS OF UNIVERSITY STUDENTS BASED ON COMPETENCE APPROACH - Ohnivchuk, Lesia М. (Educological discourse, 2014)
Evaluation of educational achievements of university students based on competence approach is a key issue of pedagogy, psychology and methodology and needs to conduct research different approaches and find effective methods such an evaluation. In this paper, we propose a mathematical model and method of evaluation the level of formation of university students competences on the basis of fuzzy logic, the expediency of its use are described features of the data processing and analysis, identified further areas of research this issue.